2020
DOI: 10.1007/s10067-020-05477-7
|View full text |Cite
|
Sign up to set email alerts
|

One-year efficacy and safety of single or one to three weekly injections of hylan G-F 20 for knee osteoarthritis: a systematic literature review and meta-analysis

Abstract: The aim of this study was to evaluate the long-term efficacy and safety of single or 1–3 weekly injections of hylan G-F 20 at 1 year following the first injection for knee osteoarthritis (OA). Searches were conducted in PubMed/MEDLINE, Embase, and CENTRAL and included relevant conference proceedings (January 1, 1995–August 17, 2020). Randomized controlled trials (RCTs), non-randomized trials, and observational studies investigating 1-year efficacy and safety of 1–3 weekly injections or single hylan G-F 20 inje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…It is important to note that product containing active biomolecules and/or genes require more complex procedures, regulation, and funding which can limit the sustainability 13 . In the US market, FDA approved cell-free hydrogel are Gel-One®, Synvisc and Synvisc-One® 165,166 . Whereas, hydrogelbased with autologous chondrocytes product include CaReS®, a type I collagen and Cartipatch®, which uses agarose-alginate hydrogel.…”
Section: Cellular Therapies For Cartilage Regenerationmentioning
confidence: 99%
“…It is important to note that product containing active biomolecules and/or genes require more complex procedures, regulation, and funding which can limit the sustainability 13 . In the US market, FDA approved cell-free hydrogel are Gel-One®, Synvisc and Synvisc-One® 165,166 . Whereas, hydrogelbased with autologous chondrocytes product include CaReS®, a type I collagen and Cartipatch®, which uses agarose-alginate hydrogel.…”
Section: Cellular Therapies For Cartilage Regenerationmentioning
confidence: 99%
“…This study evaluated a single shot consisting of a higher volume of product vs. 3 once-weekly injections of a smaller volume of product. This study focused on the specific formulation of Hylan G-F 20, which is a cross-linked higher-molecular-weight hyaluronan 10 . Measures were taken by patient ratings of Western Ontario and McMaster Universities Arthritis Index (WOMAC) scores for pain, stiffness, and function as well as the visual analog scale (VAS) pain score.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…[48] Meta-analysis pro Six months of treatment IA HA and the combination of IA HA and triamcinolone improve pain and/or physical function in patients suffering from knee OA. 2021 [50] Meta-analysis pro Hylan G-F 20 at both frequencies (either as single or 1-3 weekly injections) are efficacious and generally well tolerated for long-term use.…”
Section: Publication Year [Ref]mentioning
confidence: 99%
“…Radiologic chondrocalcinosis is not a contraindication to HA [69]. For severe OA, HA is not contraindication, but it is known to be ineffective [50]. Eymard et al have reported that IA HA should be considered only in patients with low BMI and low radiologic severity because high BMI and radiologic severity significantly increase the risk of IA HA failure [71].…”
Section: Hyaluronic Acid Contraindication and Adverse Effectsmentioning
confidence: 99%